Source-Based Routing Trees for Efficient Congestion Control in Wireless Sensor Networks - Sergiou, C.; Vassiliou, V. (2012 IEEE 8th International Conference on Distributed Computing in Sensor Systems, 2012)
Placement of nodes in Wireless Sensor Network (WSNs) is often massive and random. Topology control algorithms focus in lowering the initial network topology, by reducing active nodes and links, thus saving resources and increasing network lifetime. Currently, most algorithms and schemes in WSNs, construct shared, core-based trees, with the sink as a root for this purpose. In this paper, we study whether trees that initiate from each source, called source-based trees, can assist in this purpose and provide, under specific circumstances, an efficient topology control solution. Simulation results show that source-based trees can provide proper topology and routing control solution in WSNs, when are employed along with "resource", congestion control algorithms in WSNs.